Metabolic syndrome in south Indian population with skin tags: a hospital-based case control study - Naidu, Bobbili Tarun Kesava; Baddireddy, Kavya (International Journal of Research in Medical Sciences, 2020)
Background: Metabolic syndrome is a constellation of several clinical and laboratory cardiovascular risk factors that have been linked with numerous medical and dermatologic conditions. Recent evidence suggests a strong association between skin tags and insulin resistance and obesity, yet there is a paucity of data on relation of skin tags with metabolic syndrome as a whole. Aim of the study was to evaluate the strength of association between skin tags and metabolic syndrome. Methods: 70 patients with skin tags and an equal number of age and gender matched controls were enrolled in a hospital-based case control study. Anthropometric measures, blood pressure, fasting glucose, high density lipoprotein cholesterol and triglycerides were measured. Metabolic syndrome was diagnosed by the presence of 3 or more of the south Asian modified national cholesterol education program’s adult panel III criteria. Statistical analysis was performed using chi square test, and odds ratio was calculated. P≤0.05 were considered significant. Results: Metabolic syndrome was significantly more common in patients with skin tags than in controls (70% vs. 26%, p<0.001). Triglycerides and waist circumference values were significantly increased in cases as compared to controls (p<0.05). There was no statistically significant difference in the high-density lipoprotein levels, fasting blood glucose levels and presence of hypertension among cases and controls. Conclusion: Skin tags when present in multiple could be an early warning sign for Metabolic syndrome. They serve a cutaneous marker to initiate early detection and intervention of at-risk patients for cardiovascular disorders.